School Engagement and Context: A Multilevel Analysis of Adolescents in 31 Provincial-Level Regions in China - Liu, Fangqing; Gai, Xiaosong; Xu, Lili; Wu, Xiaojing; Wang, Hong (Frontiers in Psychology, 2021)
According to ecological system theory, both the microsystem environment (home environment) and the more macrolevel environment (provincial environment) influence school engagement in adolescents. This study tests an ecological model of adolescents’ school engagement with 19,084 middle school students across 31 provincial-level regions in China. Multilevel modeling is used to predict adolescents’ school engagement (behavior, emotion, and cognition) at two levels, individual [gender and family socioeconomic status (SES)] and provincial (economy, public cultural facilities, technological industry and education). The school engagement of students varies significantly across provincial-level regions. SES positively affects the school engagement of students. Students benefit from the provincial environment when the economy is booming, public cultural facilities are adequate and education is flourishing. The development of the technology industry fails to boost students’ school engagement. Limitations and future directions are discussed.